Insights into the historical assembly of East Asian subtropical evergreen broadleaved forests revealed by the temporal history of the tea family. Issue 3 (11th July 2017) - Yu, Xiang‐Qin; Gao, Lian‐Ming; Soltis, Douglas E.; Soltis, Pamela S.; Yang, Jun‐Bo; Fang, Liang; Yang, Shi‐Xiong; Li, De‐Zhu
Summary: Subtropical evergreen broadleaved forests (EBLFs) inhabit large areas of East Asia. Although paleovegetation reconstructions have revealed that the subtropical EBLFs existed in Southwest China during the Miocene, the historical construction of these forests remains poorly known. Here, we used the tea family (Theaceae), a characteristic component of the subtropical EBLFs, to gain new insights into the assembly of this important biome. Using a robust phylogenetic framework of Theaceae based on plastome and nuclear ribosomal DNA sequence data, the temporal history of the family was reconstructed. Data from other characteristic components of subtropical EBLFs, including Fagaceae, Lauraceae and Magnoliaceae, were also integrated. Most of the essential elements of the subtropical EBLFs appear to have originated around the Oligocene–Miocene (O–M) boundary. However, small woody lineages (e.g. Camellia, Hartia ) from Theaceae were dated to the late Miocene. Accelerated net diversification rates within Theaceae were also detected near the O–M transition period and the late Miocene. Our results suggest that two independent intensifications of the East Asian summer monsoon (EASM) around the O–M boundary and the late Miocene may have facilitated the historical assembly of the subtropical EBLFs in East Asia.